A Critical Appraisal of Employee Work Life Balance among Deposit Money Banks in Enugu State, Nigeria - Onodugo, Vincent Aghaegbunam; Chukwu, Benjamin Ibe; Nwobodo-Anyadiegwu, Eveth Nkeiruka; Ilo, Sylvester Okechukwu; Anioke, Christian Nnabuike (Journal of Reviews on Global Economics, 2019)
The increased demand on today's employees has engendered a lot of conflicts between work life and other aspects of human endeavour. This study investigated the relationship between work life and employee performance. Specifically, it examined the effect of hours of work on employee's health, assessed the relationship between flexibility of work schedule and employee turnover and determined the influence of family size on lateness to work. The study made use of survey design. Data were obtained through administration of questionnaire to 330 employees of banks operating in Enugu State, Nigeria who were selected using the stratified sampling method. Findings show that long hours of work correlated with frequent health breakdown of employees; there was a positive relationship between flexibility of work schedule and employee turnover; and family size significantly affected employees' tendencies to be late to work. Expectedly, finding provides the motivation for banks to structure work relationships to enhance productivity and reduce employees' work-life conflicts.